Administration and society in new nations principles and practices - Huque, Ahmed Shafiqul (Philippine Journal of Public Administration, 1987)
Understanding public administration in new nations presents a particularly strong challenge. The ideas developed in the West serve as useful purposes in .the new nations, too, where the administration is conducted in an entirely different situation. The colonial tradition, the complexity of administrative processes, attitude of mutual "distrust" between officials and the public, corruption, and ineptitude give rise to doubts about the applicability of the principles developed under circumstances prevailing in the West. In new nations, the process of administration is based on different assumptions and is primarily aimed at the reservation and promotion of self and group interests by the rulers and officials in societies afflicted with an acute shortage of personnel and resources. The scalar and functional principles are faithfully followed, while unity of command is often violated.